2023
DOI: 10.1186/s40317-022-00313-y
|View full text |Cite
|
Sign up to set email alerts
|

Receiver mount design, transmitter depth, and wind speed affect detection probability of acoustic telemetry transmitters in a Missouri River tributary

Abstract: Background One of the most important considerations for acoustic telemetry study designs is detection probability between the transmitter and the receiver. Variation in environmental (i.e., wind and flow) and abiotic (i.e., bathymetry) conditions among aquatic systems can lead to differences in detection probability temporally or between systems. In this study we evaluate the effect of distance, receiver mount design, transmitter depth, and wind speed on detection probabilities of two models of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…We found that detection probability was almost 100% at 100 m downstream of the receiver. The downstream line-of-sight distance at each receiver on the James River was at least 100m (Carlson et al 2023), and we are confident that any fish swimming near or past a receiver were detected.…”
Section: Methodsmentioning
confidence: 90%
See 1 more Smart Citation
“…We found that detection probability was almost 100% at 100 m downstream of the receiver. The downstream line-of-sight distance at each receiver on the James River was at least 100m (Carlson et al 2023), and we are confident that any fish swimming near or past a receiver were detected.…”
Section: Methodsmentioning
confidence: 90%
“…During the summer of 2021, we added eleven InnovaSea model Vr2Tx (n=5) and Vr2W (n=6) 69kHz (InnovaSea, Bedford, Nova Scotia) passive telemetry receivers to the existing telemetry network in the James River for a total of 21 receivers spanning from rkm 1 to rkm 358. Receivers were mounted in one of two setup designs: pipe-mounted or frame-mounted, as described in Carlson et al (2023). The receivers in pipe mounts were deployed in a 3.05 m long, 10 cm diameter polyvinyl chloride (PVC) pipe on the downstream side of round or square bridge pilings.…”
Section: Methodsmentioning
confidence: 99%